PROSEDUR AUDIT ATAS LAPORAN REALISASI ANGGARAN (LRA) - Nurdiah Anjas Kesuma; Muhammad Ilham Ismail; Dina Ristika; Widhah Raihanah; Muhammad Fauzan Ahnaf (Politeknik Negeri Sriwijaya, 2021)
The purpose of this study is to determine the audit procedures at public accounting firms in Palembang which is Kantor Akuntan Publik Drs. H. Suparman, Ak to the standard it supposed to use which is International Standard on Auditing or best known as ISA. The type of data used in this research is qualitative. The results show that the audit procedures in Kantor Akuntan Publik Drs. H. Suparman, Ak has been appropriate to ISA as its standard.